SiUinde: A collaborative platform to share conditions for near-the-shore activities - Serrão, C.; Coelho, A.; Carvalho, H.; Carvalho, N (International Conference on Information Society (i-Society 2014), 2014)
Currently, a large number of near-the-shore activities (sports and leisure) with a huge set of practitioners (growing everyday) exist. Also, the number of commercial companies, such as sport schools, that explore such type of costal activities are also on the rising. These kind of coastal activities are dependent of a set of conditions (in particular on what concerns the sun, the wind and waves) that affect directly or indirectly, the type of activity – mostly sportive – that can be practiced (surf, windsurf, paddle, kite surfing, canoeing, paragliding and others) on a given spot at a given time. This paper presents a platform, called SiUinde that was developed to allow users to collaboratively communicate reports about the coastal conditions, using several parameters, which include the wind conditions and the sea conditions, through a smartphone or tablet, permitting other users to have an in-depth and timely overview of the best places to enjoy their near-the-shore activities. This collaborative platform, takes advantage from the concept of collaborative intelligence and crowdsourcing to provide to the end-users the best possible recommendations for their preferred near-the-shore activities.